A new spectral parameter to predict dominant wave breaking based on the JONSWAP spectrum. (1st January 2022) - Xu, Yuanyuan; Liang, Shuxiu; Sun, Zhaochen; Xue, Qingren
Abstract: Finding a robust and universal diagnostic parameter that determines the onset of deep-water breaking and its strength has been challenging in wave breaking research. In this paper, a new diagnostic parameter (wave-breaking spectral parameter, WSP) is defined based on the significant steepness of the spectral peak ϵ p that was initially proposed by Banner et al. (2000) and Babanin et al. (2001) . In addition, the WSP formula contains the spectral peakedness parameter Q p and spectral width ν for taking into account the effect of spectral shape on the value of breaking threshold. To derive the WSP formula and verify the prediction ability of this diagnostic parameter, multiple wave types including nonbreaking waves, critical waves, and single and multiple breaking wave trains were generated in our experiments. The wave trains were generated using a linear focusing theory with components following the JONSWAP distribution. Results show that the threshold value of the new WSP, which distinguishes single and multiple breaking events from non-breaking waves, is found to be 0.042. Furthermore, WSP is used in isolated deep-water spilling breaking packets, and its prediction accuracy is compared with that of the kinematic criterion parameter B x . The results show that WSP has advantages in predicting the onset of wave breaking, especially for non-sharp wave conditions. Finally, the spatial variation of the total loss rate of the wave energy flux Δ F b r E ¯ ¯ Δ F b E ¯ ¯ in deep-water unsteady breaking waves was investigated. It was found that the new WSP has a strong linear correlation with the total loss rate of the wave energy flux. Considering that WSP can be mathematically expressed directly using the spectrum, WSP will be parameterized into the dissipation term of the spectral wind-wave model in our future work. It is expected that the calculation accuracy of the dissipation term will be improved, and the wave model's prediction accuracy of wave parameters will be enhanced because WSP provides a reliable wave-breaking threshold value and has a strong linear relationship with the dissipation rate. Highlights: A spectral parameter WSP is proposed based on experiments data to accurately predict the onset of dominant breaking. WSP takes into account the spectral shape and can be mathematically expressed straight from spectral. WSP provides an accurate prediction of breaking, especially for non-sharp wave conditions. WSP has a strong linear relationship with the energy loss of wave breaking.